KOMUNIKASI INTERAKSI SIMBOLIK GURU TERHADAP PENINGKATAN PRESTASI BELAJAR SISWA TUNARUNGU SLBN MEULABOH - Mildad, Jamal; Aini, Suri (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2023)
Special education teachers are one component of education that directly affects the success of children with special needs in their development. The purpose of Special Education in Special Schools (SLB) is to help students with physical or mental disorders to be able to develop attitudes, knowledge and skills. This research seeks to explore how the teacher's symbolic interaction communication improves the learning achievement of students with disabilities (deaf) at the Meulaboh State Special School by using the symbolic interaction theory proposed by George Herbert Mead. The methodology used is a qualitative research method with a descriptive analysis presentation. Data were collected by using interviews with 8 informants. The results of this study show that on the Mind indicator, the originator in communication is sign language, SIBI. However, spoken language is also used occasionally to train deaf students. Furthermore, on the Self indicator, deaf children see the teacher from another person's point of view and require following to be able to take the same role. Therefore, verbal language in the form of sound pronunciation is added to the way teachers and students communicate. Meanwhile, on the indicators of the Society, communication and interaction between teachers and students has been going well and teachers do not feel many significant obstacles because the SLB teachers apply action, interaction and transaction communication patterns. Furthermore, SLB Meulaboh students have adapted to life in society.